On the Fringes of History: Food and Eating Habits in the Banat - Harsanyi, Doina; Harsanyi, Nicolae (Petits Propos Culinaires, 1994)
Dr Nicolae Harsanyi taught English literature and language at the University of Timisoara, Romania. Doina Harsanyi, MA, taught French in the Transylvanian town of Târgu Mures until1986, when she joined the University of Timisoara as a researcher. 1n 1988 she translated into Romanian Brillat-Savarin’s classic gastronomical essay La Physiologie du Goût in 1990 both moved to the USA. After three years of teaching at the University of Michigan, Ann Arbor, Nicolae completed a year-fellowship at the National Humanities Center in North Carolina. Doina is enrolled in the PhD program in history at the University of North Carolina, Chapel Hill.